AENEAS ANCHISIADES I PII FRATRES. KILKA UWAG O KSZTAŁTOWANIU SIĘ WIZERUNKU ENEASZA W MENNICTWIE RZYMSKIM - Kluczek, Agata A. (Studia Europaea Gnesnensia, 2017)
The article discusses certain aspects of representations of Aeneas in Roman coinage, focusing in particular on the declining period of the Republic and Augustus’ principate. At the time, Aeneas; father, Anchises, would be depicted on the coins as the sole companion of the former. Although later the figure of the parent carried on a shoulder served as an attribute denoting the Trojan hero depicted on the reverses, the early minted representations of Aeneas were not as unambiguous in that respect. This was due to the fact that portrayals of Aeneas did resemble the manner in which the Catanian Brothers were represented, with both serving potentially as allegories of pietas.